BEHAVIOR OF MULTI-LAYER COMPOSITE BEAMS WITH PARTIAL INTERACTION "PART I " - I. Aziz, Khalel; M. Ali, Zeyad; I. M. Al-Amery, Riyadh (Iraqi Journal of Civil Engineering, 2007)
ABSTRACT: In this study an attempt is made to develop a method of analysis dealing with a multi-layer composite beam, for linear material and shear connector behavior in which the slip (horizontal displacement) and uplift force (vertical displacement) are taken into consideration. The analysis is based on a approach presented by Roberts[1], which takes into consideration horizontal and vertical displacement in interfaces. The analysis led to a set of eight differential equations contains derivatives of the fourth and third order. A program based on the present analysis is built. Series of three push-out tests were carried out to investigate the capacity of shear stiffness for connectors. From these tests, load-slip curves were obtained. Also, series of multi-layer composite simply supported beams were tested. Each one consists of three layers in different material properties and dimensions. A comparison between the experimental values and numerical analysis is carried out. Close agreement is obtained with experimental values for different materials, layers thickness and shear stiffness.